STUDI PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MIND MAPPING BERBASIS MINDMAPLE LITE UNTUK MENINGKATKAN REGULASI DIRI - Putro, Hijrah Eko; Japar, Muhammad (Lembaga Penelitian UM Metro, 2018)
This research was conducted with the aim of: (1) Knowing the implementation of group guidance services at Al Iman MTs in Magelang City, (2) Knowing the objective conditions of student self-regulation, (3) produce a model of group guidance services with mind mapping based lite mind mapping techniques to improve self-regulation, (4) determine the effectiveness of group guidance services with mind mapping based lite mind mapping techniques to improve self-regulation of students of MTs Al Iman in Magelang City. The population in this study was the grade IX students of MTs Al Iman in Magelang City which 22 students and used as a sample of 10 students. The research design used pre-experimental: one group pretest-posttest design with purposive sampling. Data analysis technique used is Paired sample t-Test with consideration in this study using one independent variable (Independent Variable). The results of the effectiveness test of this study are the existence of an increase in self-regulation through group guidance services with mind mapping based lite mind mapping techniques. The level of self-regulation of students has increased after participating in group guidance services with mind mapping based lite mind mapping techniques. This is seen from the increase in the results of self-regulation scale before and after being given group guidance services with mindmaple lite based mind mapping technique of 28% and strengthened through effectiveness testing using t-test which shows -t count <-t table, which is -6.040 <- 2,262 or data Sig (0,000) <0,05.